Porous particle electrode material and preparation method and application thereof
The preparation of porous particle electrode materials by one-step granulation method has solved the problems of high cost and poor structural stability of particle electrode materials in the prior art, achieved the characteristics of porous structure, high stability and low cost, and improved the degradation efficiency of sulfonamide wastewater.
Patent Information
- Application Number
- CN202411892270.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the prior art, particle electrode materials have problems such as high cost, poor structural stability and solidification, resulting in underutilization of catalytic active sites and low degradation efficiency.
By using one-step granulation method, the furnace slag, pore-forming agent and waste ternary battery filler are mixed in an acid or alkali solution, and after calcination, a porous and porous particle electrode material with strong structural stability is prepared.
The porous structure, high structural stability and low cost of porous particle electrode materials are achieved, the adsorption of persulfate and the generation capacity of reactive oxygen species are improved, and the degradation efficiency of sulfonamide wastewater is improved.
Smart Images

Figure CN119797507A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental electrochemistry, and relates to a porous particle electrode material and a preparation method and application thereof, and in particular to a porous particle electrode material with strong structural stability and a preparation method thereof, and application thereof in enhancing the degradation of sulfonamide wastewater by electro-activated persulfate. Background Art
[0002] Antimicrobial drugs are widely used in animal husbandry, medical treatment and aquaculture to treat and prevent bacterial infections. Excessive use of antibiotics will inhibit and interfere with the growth and reproduction of aquatic organisms in water bodies, and cause many serious environmental problems, such as bacterial resistance and biological toxicity. Such substances often enter the water environment again with excrement. At present, the technologies for treating antibiotic wastewater include biological methods, physical and chemical methods, and chemical methods. Among them, biological methods usually require additional nutrients and appropriate environmental conditions to meet the growth of microorganisms. Therefore, they are not suitable for removing antibiotic pollution in wastewater. Physical and chemical methods mainly include ion exchange and reverse osmosis, but both of them only separate antibiotics from water, and the high-concentration antibiotic wastewater produced needs further treatment. The commonly used chemical method is catalytic hydrogenation, but the production, transportation and storage of hydrogen are also a major problem currently faced. In comparison, electrocatalytic oxidation technology has the characteristics of mild reaction conditions, no secondary pollution, flexibility, simplicity and controllability of water treatment. However, this technology also faces some challenges. For example, ① many particle electrodes currently under development are solid, and the catalytic active sites inside them are not functioning, resulting in catalysis occurring only on their surface; ② many particle electrode materials have poor structural stability; and ③ the preparation cost of particle electrode materials is expensive.
[0003] In view of this, it is necessary to provide a new type of particle electrode material that is porous, has strong structural stability and is low in cost, so as to solve or at least alleviate the above-mentioned defects of high cost, poor structural stability and solid particle electrode. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, especially the defects of the prior art such as high cost, poor structural stability and solid particle electrodes, and to provide a porous, structurally stable and low-cost porous particle electrode material and its preparation method and application.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0006] A method for preparing a porous particle electrode material comprises the following steps: adding slag, a pore-forming agent and a waste ternary battery filler into a solution, wherein the solution is an acid solution or an alkaline solution, granulating the granules by a one-step granulation method, and then calcining the granules at 250°C to 650°C to obtain the porous particle electrode material.
[0007] In the above-mentioned method for preparing the porous particle electrode material, preferably, the ratio of the slag, the pore-forming agent, the waste ternary battery filler and the solution is 100.0g~50.0g: 0.1g~1.0g: 1.0g~10.0g: 10mL~30mL.
[0008] In the above-mentioned method for preparing the porous particle electrode material, preferably, the acid solution is one or more of sulfuric acid solution, hydrochloric acid solution and nitric acid solution, the mass fraction of the acid in the acid solution is 5% to 10%, and the temperature of the acid solution is 50°C to 80°C; the alkaline solution is one or more of sodium hydroxide solution, potassium hydroxide solution and ammonia water, the mass fraction of the alkali in the alkaline solution is 5% to 10%, and the temperature of the alkaline solution is 50°C to 80°C.
[0009] In the above-mentioned method for preparing the porous particle electrode material, preferably, the slag contains 10% to 30% by mass of iron oxide and 30% to 45% by mass of aluminum oxide, and the particle size of the slag is 200 mesh to 600 mesh; the pore-forming agent is one or more of graphite powder, activated carbon powder, paraffin, calcium carbonate and ammonium bicarbonate; the waste ternary battery filler contains more than 90% by mass of nickel, cobalt, manganese and lithium or more than 90% by mass of nickel, cobalt, aluminum and lithium, and the particle size of the waste ternary battery filler is 200 mesh to 600 mesh.
[0010] In the method for preparing the porous particle electrode material, preferably, the calcination time is 1 h to 6 h.
[0011] In the above-mentioned method for preparing the porous particle electrode material, preferably, the particle size of the porous particle electrode material is 0.1 cm to 1 cm, and the pore size is 10 nm to 30 nm.
[0012] In the above-mentioned method for preparing the porous particle electrode material, it is more preferred that the particle size of the porous particle electrode material is 0.35 cm to 0.65 cm.
[0013] As a general technical concept, the present invention also provides a porous particle electrode material prepared by the above-mentioned method for preparing the porous particle electrode material.
[0014] As a general technical concept, the present invention also provides an application of the above-mentioned porous particle electrode material in enhancing the degradation of sulfonamide wastewater by electro-activated persulfate.
[0015] The above application, preferably, comprises the following steps: using a ruthenium iridium titanium plate as an anode and a stainless steel plate as a cathode, adding the porous particle electrode material into an electrolytic cell containing sulfonamide wastewater, an electrolyte and a catalyst, adjusting the pH value to 4 to 10, and reacting under constant current conditions to enhance the degradation of sulfonamide wastewater by electro-activated persulfate; the mass concentration of sulfonamide in the sulfonamide wastewater is 50 mg / L to 200 mg / L, the electrolyte is one or more of sodium chloride, anhydrous sodium sulfate and sodium nitrate, and the electrolyte is in the sulfonamide wastewater. The molar concentration in the wastewater is 0.25mmol / L to 1.0mmol / L, the catalyst is at least one of potassium persulfate, sodium persulfate, potassium persulfate composite salt and sodium persulfate composite salt, the molar concentration of the catalyst in the sulfonamide wastewater is 0.10mmol / L to 0.75mmol / L, the mass ratio of the porous particle electrode material to the volume of the sulfonamide wastewater is 20g to 50g: 150mL to 200mL, and the current density used in the constant current condition is 6mA / cm 2 ~20mA / cm 2 .
[0016] Compared with the prior art, the advantages of the present invention are:
[0017] 1. The preparation method of the present invention adopts a one-step granulation method through precise material design and synthesis, and coordinates the synergistic effect of three materials: slag, waste ternary battery filler and pore-forming agent. By precisely controlling the dosage of the pore-forming agent, the dosage of slag and the ratio of the catalytically active material (waste ternary battery filler), the porous structure, high structural stability and low cost of the porous particle electrode material are achieved.
[0018] At present, many particle electrodes have the disadvantages of being solid, having poor structural stability, having a small specific surface area and having high cost. The porous particle electrode material prepared by the present invention has the following characteristics: low material cost (turning waste into treasure), simple electrode preparation process, good degradation effect and strong structural stability. These characteristics are conducive to the wide application of the porous particle electrode material of the present invention in wastewater such as urban sewage, groundwater and industrial wastewater contaminated with sulfonamide.
[0019] 2. The porous particle electrode material of the present invention can be used to enhance the degradation of sulfonamide wastewater by electro-activated persulfate. The porous structure characteristics of the porous particle electrode material can provide the electrode with a higher specific surface area and more active sites, promote the adsorption of persulfate (PMS), and thus facilitate the production of more active oxygen species. The high structural stability and low cost characteristics of the porous particle electrode material are conducive to the advancement of industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the porous particle electrode material prepared in Example 1 of the present invention.
[0021] Figure 2 This is a diagram showing the effect of the porous particle electrode material prepared in Example 1 of the present invention on the degradation of sulfonamide wastewater by electro-activation of persulfate at different current densities for 1.5 hours.
[0022] Figure 3 This is a comparison chart of the effects of using porous particle electrode materials prepared with different amounts of pore-forming agents in Example 2 of the present invention to electro-activate persulfate to degrade sulfonamide wastewater for 1.5 hours.
[0023] Figure 4 This is a comparison chart of the effects of the porous particle electrode material in Example 3 of the present invention being applied to the degradation of sulfonamide wastewater by electro-activation of persulfate for 10 cycles.
[0024] Figure 5 This is a diagram showing the effect of the porous particle electrode material in Example 4 of the present invention electrically activating persulfate to degrade sulfonamide wastewater in the environmental protection workshop of a pharmaceutical company in Changsha for 1.5 hours.
[0025] Figure 6 This is a diagram showing the effect of electro-activating persulfate to degrade sulfonamide wastewater for 1.5 hours without porous particle electrode materials in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. In the following examples, unless otherwise specified, the materials and instruments used are commercially available, the processes used are conventional processes, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0027] Example 1
[0028] A method for preparing a porous particle electrode material of the present invention comprises the following steps:
[0029] (1) Soak 100g of slag in a dilute hydrochloric acid solution containing 0.5g of pore-forming agent and 10g of waste ternary battery filler, the pore-forming agent is ammonium bicarbonate, the slag contains 20wt% of iron oxide and 45wt% of aluminum oxide, the particle size of the slag is 400 mesh, the waste ternary battery filler contains 92% by mass of nickel, cobalt, aluminum and lithium, the particle size of the waste ternary battery filler is 450 mesh, the volume of the dilute hydrochloric acid solution is 30mL, the mass fraction of hydrochloric acid in the dilute hydrochloric acid solution is 5%, the temperature of the dilute hydrochloric acid solution is 55°C, and the soaking time is 2h. The obtained mixture is placed in a granulator for granulation, and then the obtained spherical particles are placed in a muffle furnace and calcined at 550°C for 2h to obtain a porous particle electrode material with a particle size of 0.45cm~0.55cm and a pore size of 10nm~30nm. Figure 1It can be seen that in the porous particle electrode material prepared in Example 1, the catalytically active metal substances (cobalt, nickel, manganese) in the waste ternary battery are uniformly loaded on the surface of the particle electrode. In addition, the surface of the particle electrode is rough and has many pore structures.
[0030] An application of the porous particle electrode material of this embodiment in enhancing the electro-activated persulfate degradation of sulfonamide wastewater comprises the following steps:
[0031] S1. Prepare cathode plates and anode plates. The cathode is a stainless steel plate of 10 cm × 10 cm × 0.2 cm. The anode is a commercial electrode ruthenium iridium titanium plate with a size of 10 cm × 10 cm × 0.2 cm. Sulfonamide wastewater, electrolyte and catalyst are added to the electrolytic cell in sequence. The concentration of sulfonamide in the sulfonamide wastewater is 100 mg / L. The sulfonamide wastewater is 200 mL. The electrolyte is anhydrous sodium sulfate. The molar concentration of the electrolyte in the sulfonamide wastewater is 0.25 mmol / L. The catalyst is potassium persulfate complex salt (purity above 98%, Shanghai Titan Technology Co., Ltd.), and the molar concentration of the catalyst in the sulfonamide wastewater is 0.30 mmol / L.
[0032] S2. Use dilute hydrochloric acid and dilute sodium hydroxide solution to adjust the pH value of the above wastewater to 7.0, then place 50g of porous particle electrode material in the above electrolytic cell, and conduct the electrolysis at current densities of 6, 8, 10, 12, and 14 mA / cm 2 The degradation was carried out under constant current conditions for 1.5 h. The results are shown in Figure 2 shown.
[0033] Depend on Figure 2 It can be seen that in this embodiment, when the current density is increased from 6mA / cm 2 Increase to 14mA / cm 2 When the current density exceeds 12 mA / cm, the removal efficiency of sulfonamide increases from 74.12% to 99.98%, indicating that the increase of current density can enhance the degradation performance of sulfonamide. 2 The post-degradation efficiency no longer changes.
[0034] Example 2
[0035] A method for preparing a porous particle electrode material of the present invention comprises the following steps:
[0036] (1) 100g of slag is soaked in a dilute hydrochloric acid solution containing 0g, 0.25g, 0.5g, 0.75g, 1.0g of ammonium bicarbonate and 10g of waste ternary battery filler, respectively. The slag contains 20wt% of iron oxide and 45wt% of aluminum oxide, the particle size of the slag is 400 mesh, the waste ternary battery filler contains 92% by mass of nickel, cobalt, aluminum and lithium, the particle size of the waste ternary battery filler is 450 mesh, the mass fraction of hydrochloric acid in the dilute hydrochloric acid solution is 5%, the volume of the dilute hydrochloric acid solution is 30mL, the temperature of the dilute hydrochloric acid solution is 55℃, the soaking time is 2h, the obtained mixed material is placed in a granulator for granulation, and then placed in a muffle furnace for calcination at 550℃ for 2h to obtain a porous particle electrode material with a particle size of 0.45cm-0.55cm and a pore size of 10nm-30nm. Table 1 shows the specific surface area of the porous particle electrode material in this embodiment under different ammonium bicarbonate addition conditions.
[0037] Table 1 Specific surface area results of porous particle electrode materials under different ammonium bicarbonate dosage conditions
[0038]
[0039]
[0040] The porous particle electrode material of this embodiment (different amounts of pore-forming agents are added during the preparation process) is used to enhance the electro-activated persulfate degradation of sulfonamide wastewater. The process is basically the same as that of Example 1, except that: at a current density of 12 mA / cm 2 The electro-activated persulfate was used to degrade sulfonamide wastewater under constant current conditions for 1.5 h. The results are shown in Figure 3 shown.
[0041] From Table 1 and Figure 3 It can be seen that the specific surface area of the porous particle electrode material increases with the increase of the pore-forming agent ammonium bicarbonate, and the degradation efficiency of sulfonamide also increases with the increase of the pore-forming agent ammonium bicarbonate, but after exceeding 0.5g, its specific surface area and sulfonamide removal rate will hardly change. Therefore, the optimal dosage of ammonium bicarbonate is 0.5g.
[0042] Example 3
[0043] A porous particle electrode material and a preparation method thereof of the present invention are the same as those in Example 1.
[0044] The application of the porous particle electrode material of this embodiment in enhancing the electro-activated persulfate degradation of sulfonamide wastewater is basically the same as that of Example 1, except that: 2The persulfate was electro-activated to degrade sulfonamide wastewater for 1.5 h under constant current conditions, and then the porous particle electrode material was electro-catalytically degraded ten times under the same degradation process conditions. Table 2 shows the mass loss rate of the porous particle electrode material in this embodiment after ten cycles.
[0045] Table 2 Mass loss rate of porous particle electrode materials after ten cycles
[0046] Cycle times Mass(g) Mass loss rate (%) 0 50.0 0 1 49.715 0.57 2 49.505 0.99 3 49.29 1.42 4 49.08 1.84 5 48.7 2.26 6 48.66 2.68 7 48.445 3.11 8 48.245 3.51 9 48.035 3.93 10 47.825 4.35
[0047] Figure 4 The porous particle electrode material in this embodiment is used to enhance the effect of electric field activation persulfate degradation of sulfonamide for 10 cycles. The sulfonamide removal rate is only reduced from 99.98% to 99.63% after 10 cycles, indicating that the porous particle electrode material has excellent stability. In addition, it can be seen from Table 2 that after 10 cycles, the mass loss rate of 50g material only decreases by 4.35%. Based on the above data, it can be shown that the porous particle electrode material of the present invention has good structural stability.
[0048] Example 4
[0049] A porous particle electrode material and a preparation method thereof of the present invention are the same as those in Example 1.
[0050] An application of the porous particle electrode material of this embodiment in enhancing the electro-activated persulfate degradation of sulfonamide wastewater comprises the following steps:
[0051] S1. Prepare cathode and anode plates, with the cathode using a stainless steel plate of 10cm×10cm×0.2cm, and the anode using a commercial electrode ruthenium-iridium-titanium plate with a size of 10cm×10cm×0.2cm. Add 200mL of sulfonamide wastewater, electrolyte and catalyst from the environmental protection workshop of a pharmaceutical company in Changsha to the electrolytic cell in sequence, wherein the concentration of sulfonamide in the sulfonamide wastewater is 125.6mg / L, the electrolyte is anhydrous sodium sulfate, and the molar concentration of the electrolyte in the sulfonamide wastewater is 0.25mmol / L, the catalyst is potassium persulfate complex salt (purity above 98%, Shanghai Titan Technology Co., Ltd.), and the molar concentration of the catalyst in the sulfonamide wastewater is 0.30mmol / L.
[0052] S2. Use dilute hydrochloric acid and dilute sodium hydroxide solution to adjust the pH value of the above wastewater to 7.0, then place 50g of porous particle electrode material in the above electrolytic cell and conduct the electrolysis at a current density of 12mA / cm 2 The degradation was carried out under constant current conditions for 1.5 h. The results are shown in Figure 5 As shown. Figure 5 It can be seen that the removal rates of sulfonamide and TOC (total organic carbon) in the wastewater reached 98.65% and 50.26% respectively.
[0053] Based on the above results, it can be seen that the porous particle electrode material prepared by the present invention has a good degradation efficiency for both simulated wastewater and real wastewater, indicating that the porous particle electrode material has a strong potential for industrial application.
[0054] Comparative Example 1
[0055] A method for degrading sulfonamide wastewater with electro-activated persulfate is basically the same as the application process of Example 1, except that: under the condition of not containing the porous particle electrode material of Example 1, at a current density of 12 mA / cm 2 The electro-activated persulfate was used to degrade sulfonamide wastewater under constant current conditions for 1.5 h. The results are shown in Figure 6 shown.
[0056] Depend on Figure 6 It can be seen that when electro-activated persulfate is used to degrade sulfonamide wastewater, the absence of porous particle electrode material will cause the degradation efficiency to drop significantly from 99.98% to 52.21%. This shows that the porous particle electrode material of the present invention can indeed enhance the performance of electric field activated persulfate in degrading sulfonamide.
[0057] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a porous particle electrode material, characterized in that: The following steps are involved: Slag, pore former and waste ternary battery filler are added into a solution, which is an acid solution or an alkaline solution, granulated by a one-step granulation method, and then calcined at 250°C to 650°C to obtain a porous particle electrode material.
2. The method for preparing a porous particle electrode material according to claim 1, characterized in that: The ratio of the slag, the pore-forming agent, the waste ternary battery filler and the solution is 100.0 g to 50.0 g: 0.1 g to 1.0 g: 1.0 g to 10.0 g: 10 mL to 30 mL.
3. The method for preparing a porous particle electrode material according to claim 1, characterized in that: The acid solution is one or more of sulfuric acid solution, hydrochloric acid solution and nitric acid solution, the mass fraction of the acid in the acid solution is 5% to 10%, and the temperature of the acid solution is 50° C. to 80° C.; the alkali solution is one or more of sodium hydroxide solution, potassium hydroxide solution and ammonia water, the mass fraction of the alkali in the alkali solution is 5% to 10%, and the temperature of the alkali solution is 50° C. to 80° C.
4. The method for preparing a porous particle electrode material according to claim 1, characterized in that: The slag contains 10% to 30% by mass of iron oxide and 30% to 45% by mass of aluminum oxide, and the particle size of the slag is 200 mesh to 600 mesh; the pore-forming agent is one or more of graphite powder, activated carbon powder, paraffin, calcium carbonate and ammonium bicarbonate; the waste ternary battery filler contains more than 90% by mass of nickel, cobalt, manganese and lithium or more than 90% by mass of nickel, cobalt, aluminum and lithium, and the particle size of the waste ternary battery filler is 200 mesh to 600 mesh.
5. The method for preparing a porous particle electrode material according to any one of claims 1 to 4, characterized in that: The calcination time is 1 h to 6 h.
6. The method for preparing a porous particle electrode material according to any one of claims 1 to 4, characterized in that: The particle size of the porous particle electrode material is 0.1 cm to 1 cm, and the pore size is 10 nm to 30 nm.
7. The method for preparing a porous particle electrode material according to claim 6, characterized in that: The particle size of the porous particle electrode material is 0.35 cm to 0.65 cm.
8. A porous particle electrode material prepared by the method for preparing a porous particle electrode material according to any one of claims 1 to 7.
9. Use of the porous particle electrode material as claimed in claim 8 in enhancing the degradation of sulfonamide wastewater by electro-activated persulfate.
10. The use according to claim 9, characterized in that: The application comprises the following steps: using a ruthenium-iridium-titanium plate as an anode and a stainless steel plate as a cathode, adding the porous particle electrode material into an electrolytic cell containing sulfonamide wastewater, an electrolyte and a catalyst, adjusting the pH value to 4-10, and reacting under constant current conditions to enhance the degradation of sulfonamide wastewater by electro-activated persulfate; the mass concentration of sulfonamide in the sulfonamide wastewater is 50 mg / L-200 mg / L, the electrolyte is one or more of sodium chloride, anhydrous sodium sulfate and sodium nitrate, the molar concentration of the electrolyte in the sulfonamide wastewater is 0.25 mmol / L-1.0 mmol / L, the catalyst is at least one of potassium persulfate, sodium persulfate, potassium persulfate composite salt and sodium persulfate composite salt, the molar concentration of the catalyst in the sulfonamide wastewater is 0.10 mmol / L-0.75 mmol / L, the mass ratio of the porous particle electrode material to the volume of the sulfonamide wastewater is 20 g-50 g: 150 mL-200 mL, and the current density used under the constant current condition is 6 mA / cm 2 ~20mA / cm 2 .
Citation Information
Patent Citations
Blast furnace metallurgical slag based particle electrode and preparation method thereof
CN104276811A
Three dimensional-similar electro-Fenton water treatment system and method used for treating sulfamethoxazole
CN107473539A
Three-dimensional electrochemical-ozonation coupling treatment device for wastewater difficult to treat, and wastewater treatment method
CN113173626A
Method for preparing {010} crystal face exposed flaky single- crystal ternary electrode material by regenerating a waste lithium ion battery
CN113265704A
Safe pyrolysis impurity removal method for waste lithium battery and application of safe pyrolysis impurity removal method
CN113540603A